Optimization and Hydration Mechanism of Composite Cementing Material for Paste Filling in Coal Mines - Jinxiao Liu; Wenxin Li; Feng Zhang; Xinguo Zhang; Lianjun Chen; Yongle Liu (Advances in Materials Science and Engineering)
The low early strength of materials for paste filling in mines caused by low early strength of composite cementing material has been a severe issue. In this study, the effects of sulphoaluminate cement and gypsum on strengths of composite cementing material were investigated experimentally by employing the constrained formulation uniform design. With the content of the sulphoaluminate cement below 14% and the content of the gypsum below 16%, the compressive strengths of composite cementing materials increased, especially early strength. However, the initial and final setting time does not meet the engineering requirements in this case. Optimization tests of composite additives demonstrated that H2BO3(0.3%) + Na2SO4(0.1%) and H2BO3(0.3%) + NaNO2(0.1%) were ideal setting retarding and early strengthening composite additives as they can both reduce the initial and final setting time and enhance compressive strengths of composite cementing material. Investigations by XRD and SEM revealed that the hydration products of composite cementing material were dominated by AFt (ettringite) at the early stage and by C-S-H (hydrated calcium silicate) gel + CH (calcium hydroxide) gel at the middle and late stages. The hydration products of ratio-optimized composite cementing material do not restrain each other due to the generation sequence. Instead, they grew interactively and were coupled, thus facilitating the growth of the hardened body. This study can provide references for optimization of composite cementing material for paste filling in coal mines.